Industrial textile wastewater treatment via membrane photocatalytic reactor (MPR) in the presence of ZnO-PEG nanoparticles and tight ultrafiltration. (October 2019) - Desa, Amira Liyana; Hairom, Nur Hanis Hayati; Ng, Law Yong; Ng, Ching Yin; Ahmad, Mohd Khairul; Mohammad, Abdul Wahab
Highlights: Industrial textile wastewater treatment via membrane photocatalytic reactor (MPR). The potential of ZnO-PEG nanoparticles in MPR for textile wastewater treatment. Mechanisms of membrane fouling for optimum condition were studied using model fitting according to the Wiesner and Aptel equations. Abstract: In the present study, the degradation of industrial textile wastewater (SDWW) was investigated using a membrane photocatalytic reactor (MPR) in the presence of zinc oxide capped with polyethylene glycol (ZnO-PEG) nanoparticles and polypiperazine-amide (PPA) tight ultrafiltration membrane (UF-PPA). The optimum operating conditions of MPR were obtained under initial pH 11, 0.10 g/L of ZnO-PEG nanoparticles, and 75% dilution of SDWW. Field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM) analyses confirmed that ZnO-PEG nanoparticles and the UF-PPA membrane have great potential as an alternative treatment to meet the stringent discharge limits. The mechanisms of membrane fouling for the optimum operational condition were investigated using model fitting according to the Wiesner and Aptel equations. It was revealed that cake formation occurred rapidly at both stages of the fouling mechanism. Hence, it is believed that this integrated approach has a great potential to be implemented in the industrial textile wastewater treatment sector to ensure the environmental cleanliness for future generations.